Transaksi (Akad) dalam Perspektif Hukum Islam - Yusdani Yusdani (Millah: Journal of Religious Studies, 2002)
This article investigates the transactions in social affairs from Islamic Law point of view. Based on the understanding of Quranic verses, Prophet Tradition, and the basic principles of Islamic Law, it is clearly stated that every form of transaction in Islamic Law regarding social affairs problem is principally permitted as long as not contrary to the basic of Islamic teaching. In this sense, Muslims are free to formulate new kinds of transaction, agreement or contract in accordance with the need and the challenge of their lives. In other words, the form of contract in Islamic Lawis not limited only to those declared in the books of fiqh according to the schools of Islamic law. Actually Islamic Law relating to social affairs does not determine definite form of contract because the determining definite form of contract emerges the difficulties of Muslims lives. In this respect clearly that the goal of Islamic legislation is the promotion of public interest. So, to solve new challenge of contemporary economic problem, Islamic Law prepares the ethics and basic principle.